ANALISIS KEPUASAN PENGUNJUNG ATAS LAYANAN KANTOR PELAYANAN, PENYULUHAN DAN KONSULTASI PERPAJAKAN DALAM PRESPEKTIF EKONOMI SYARIAH - Pifqi Farika Azzahra (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2025)
KP2KP Majenang is the parent tax office of KPP Pratama Cilacap. As a government organization that carries out its duties in collecting State revenue and at the same time is obliged to provide services to the community, the role and function of the Directorate General of Taxes is becoming increasingly important. Good service quality is one of the efforts to increase taxpayer compliance. Self-service in the tax sector can be interpreted as services provided to Taxpayers by the Directorate General of Taxes to help Taxpayers fulfill their tax obligations Tax services are included in public services because they are carried out by government agencies, aim to meet the needs of the community and in the context of the implementation of the law and are not profit-oriented. KP2KP Majenang has a five-star rating for service satisfaction in google reviews. Overall, visitor satisfaction with the service at the tax office